The regulatory roles of circular RNAs via autophagy in ischemic stroke - Li, Xiaoqin; Li, Lingfei; Si, Xiaoli; Zhang, Zheng; Ni, Zhumei; Zhou, Yongji; Liu, Keqin; Xia, Wenqing; Zhang, Yuyao; Gu, Xin; Huang, Jinyu; Yin, Congguo; et al. (Frontiers in Neurology, 2022)
Ischaemic stroke (IS) is a severe disease with high disability, recurrence, and mortality rates. Autophagy, a highly conserved process that degrades damaged or ageing organelles and excess cellular components to maintain homeostasis, is activated during IS. It influences blood-brain barrier integrity and regulates apoptosis. CircularRNAs (circRNAs) are novel non-coding RNAs involved in IS-induced autophagy and participate in various pathological processes following IS. In addition, they play a role in autophagy regulation. This review summarises current evidence on the roles of autophagy and circRNA in IS and the potential mechanisms by which circRNAs regulate autophagy to influence IS injury. This review serves as a basis for the clinical application of circRNAs as novel biomarkers and therapeutic targets in the future.